PENGARUH GOOD CORPORATE GOVERNANCE, DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN - DWI PUTRI KARTIKA SARI; RIKI SANJAYA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The objective of this research to investigate the influence of good corporate governance and firm’s characteristic on firm value as a firm’s strategy to upgrade their value. This study use financial statement from non financial firm in Bursa Efek Indonesia for three years, start from 2014 – 2016. This study using purposive sampling method for determine a sample is required and using multiple regression and statistic descriptive for analyze data. The result of this study is four of eight variable independen influence on firm value. Independent commissioner, size of commissioner, Return on Equity, and Leverage as a component of good corporate governance influence firm value. But another good corporate governance’s component like managerial ownership, institusional ownership, audit committee, and component of firm’s characteristic there is firm size don’t effect firm value.